Seeing without the Occipito-Parietal Cortex: Simultagnosia as a Shrinkage of the Attentional Visual Field - François Michel; Marie-Anne Henaff (Behavioural Neurology)
Following bi-parietal lesions patient AT showed a severe inability to relocate her attention within a visual field which perimetry proved to be near-normal. An experimental approach with tasks testing visuo-spatial attention demonstrated a shrinkage of A.T.’s attentional visual field. With her visual attention narrowed to a kind of functional tunnel vision, the patient exhibited simultanagnosia (Wolpert, 1924), a symptom previously described in 1909 by Balint under the label of Psychic paralysis of “Gaze”. In striking contrast AT showed an efficient and effortless perception of complex natural scenes, which, according to recent work in normal subjects, necessitate few if any attentional resources.